A decade of clinical research on clinical characteristics, medical treatments, and surgical treatments for individuals with craniofacial microsomia: What have we learned?. Issue 6 (June 2022) - Renkema, Ruben W.; Caron, Cornelia J.J.M.; Heike, Carrie L.; Koudstaal, Maarten J.
Abstract: Aim: This article provides a review of a decade of clinical research studies on clinical features, medical interventions, and surgical interventions for individuals with craniofacial microsomia (CFM). We also provide recommendations for future clinical research. Method: A systematic search of literature was conducted in Embase and PubMed/MEDLINE Ovid. All publications from 2010 to 2020 that included at least 10 individuals with CFM were considered relevant for this study. Results: A total of 91 articles were included. In the past decade, many new studies on CFM have been published providing more insight on the diagnosis and management of patients with CFM. This review encompasses findings on the clinical difficulties patients with CFM encounter, including the craniofacial and extracraniofacial characteristics of patients with CFM and its related clinical consequences on breathing, feeding, speech, and hearing. Conclusions: A considerable number of large multicenter studies have been published in recent years, providing new insights in the clinical consequences of CFM. The phenotypic variety between patients with CFM makes patient-specific treatment tailored to individual needs essential. The research and development of clinical care standards might be challenging because of the heterogeneity of CFM. Future research on clinical and patient-reported outcomes can help identify optimal treatment strategies. Cooperation between craniofacial centers, using uniform registration and outcome measurement tools, could enhance research and future care for these patients. Level of evidence: Level IV.